2018
DOI: 10.4067/s0719-81322018000100110
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the nutritional state before the breeding period and the reproductive success in alpacas (Vicugna pacos) from the Chilean Puna

Abstract: ABSTRACT.A poor nutritional state may explain the low fertility rates of domestic camelids from Puna herds. The objective of this study was to determine the relationship between the nutritional state of alpacas before the breeding period and their reproductive success. The body live weight (BLW) and body condition score (BCS; scale from 1-5) of 35 non-pregnant non-lactating alpacas from the Caquena bofedal in Chile were registered previous to the breeding period. In addition, blood samples were collected (hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Van Saun (2009) indicated that pregnant alpacas under conditions of nutritional energy balance have NEFA values of less than 0.4 mEq/l (equivalent to 0.4 mmol/l), lower than the values found in this study. Also, the NEFA values of all groups were similar to those found in non-pregnant alpacas during the dry season in the Chilean altiplano (Norambuena et al 2018). Regarding β-hydroxybutyrate levels, fasting increased the β-hydroxybutyrate plasma concentration up to about 1 to 2 mg/dl (equivalent to 0.1 to 0.19 mmol/l) in non-pregnant domestic camelids (Van Saun and Cebra 2014), which is similar to the ketone values obtained for all the groups in the present study.…”
Section: Resultssupporting
confidence: 74%
“…Van Saun (2009) indicated that pregnant alpacas under conditions of nutritional energy balance have NEFA values of less than 0.4 mEq/l (equivalent to 0.4 mmol/l), lower than the values found in this study. Also, the NEFA values of all groups were similar to those found in non-pregnant alpacas during the dry season in the Chilean altiplano (Norambuena et al 2018). Regarding β-hydroxybutyrate levels, fasting increased the β-hydroxybutyrate plasma concentration up to about 1 to 2 mg/dl (equivalent to 0.1 to 0.19 mmol/l) in non-pregnant domestic camelids (Van Saun and Cebra 2014), which is similar to the ketone values obtained for all the groups in the present study.…”
Section: Resultssupporting
confidence: 74%
“…Not only a low BCS has an influence, but also strong deviations from the optimal BCS in both directions can affect the fertility cycle (Van Saun 2008 ). However, Norambuena et al investigated the reproductive success of female alpacas in terms of nutritional status and found no differences in the BCS between 20 pregnant and 15 non-pregnant animals (Norambuena et al 2018 ). In male alpacas, there is a positive correlation between BCS and testicular length, which has an influence on sperm production (Abraham et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Llamas from the Restricted group maintained the homeostasis of proteins, lipids, carbohydrates, and energy; the values of metabolic markers were according to the referential values reported for camelids (39,40). Negative energy balance (NEB) increased plasma concentrations of NEFA, BHB, or urea in previous studies conducted in llamas, alpacas, and vicuñas (17,23,41,42). Starvation or dietary insufficiency results in mobilization of adipose stores, characterized by an increase in blood NEFA (over 0.6 mmol/L), and a mild increase in blood BHB (over 0.1 to 0.19 mmol/L) in camelids (43,44).…”
Section: Discussionmentioning
confidence: 93%